LEGAL PRACTICES OF INSOLVENCY AND BANKRUPTCY IN INDIA - Dr. Sushama Yadav (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Bankruptcies have historically followed the business cycle closely. Failure of certain company strategies is a natural part of the market economy’s process. When a firm fails, the optimum outcome for society is a quick renegotiation between financiers, to fund the going concern with a new structure of obligations and a new management team. The purpose of bankruptcy legislation is to recover an entity’s debt and distribute its assets among competing claimholders. As a result, the RBI’s asset quality reviewers identified an extremely high number of NPAs. The government’s most major change is the insolvency and bankruptcy legislation. On the heels of the adoption of the Insolvency and Bankruptcy Code, India jumpedfrom 108thto 52nd in the resolving insolvency category, while its rating improved significantly in dealing with construction permits to 27th from 52nd and trading across borders to 68th from 80th. The purpose of this study is to look into the regulatory framework in India for insolvency and bankruptcy. The impact of insolvency and bankruptcy Code on the Indian economy is also discussed in the study.